Neurodevelopmental Outcome and Adaptive Behavior in Preterm Multiples and Singletons at 1 and 2 Years of Corrected Age - Squarza, Chiara; Gardon, Laura; Giannì, Maria Lorella; Frigerio, Andrea; Gangi, Silvana; Porro, Matteo; Mosca, Fabio; Picciolini, Odoardo (Frontiers in Psychology, 2020)
Background: Recent literature has investigated the role of multiple birth on neurodevelopmental outcomes of premature infants, especially extremely preterm ones. Multiple gestations are thought to be associated with increased neurodevelopmental disability. Actually, research findings are controversial. Objective: To compare the neurodevelopmental and behavioural outcomes of multiples and singletons in a cohort of preterm infants with gestational age ≤ 28 weeks at 1 and 2 years of corrected age. Methods: The study included 86 infants, born from January 2014 to September 2017 and enrolled after discharge in the follow-up programme provided at authors’ Institution. Exclusion criteria included: major brain lesions and malformations, severe neuro-sensorial deficits, genetic syndromes, single-twin survivors. 34 multiples were compared to 52 singletons, using the Griffiths Mental Development Scales and the Child Behaviour Checklist 1½-5. Statistical analysis was based on ANOVA techniques to test group differences. Statistical significance was considered for p-value <0.05. Results: The neurodevelopmental outcomes of multiples and singletons at one and two years of corrected age did not significantly differ at a general level (p>.05). Multiples showed significantly lower mean scores than singletons at one year in Locomotor (87.15±11.94 vs 92.48±11.59) and Personal-Social (84.88±10.25 vs 89.63±8.19) subscales. Considering the behavioural outcomes, higher rates of externalizing problems were observed in multiples at two years (54.27±9.64 vs 49.31±10.39). Conclusion: The slightly lower neurodevelopmental outcome showed by multiples, especially in the gross-motor and personal-social domains at one year, might be related to the specific environmental condition they experience. Multiple birth may compromise mother’s ability to provide sensitive parenting to each infant and infants’ acquisition of emotional and behavioral regulation. This affects the separation process and the acquisition of the independent walking and other gross-motor skills. Being multiples might also induce an hyperstimulation and this could explain their higher vulnerability to externalizing problems (impulsiveness, hyperactivity, attention deficits). Additionally, males are more affected by the multiple condition than females.